AI and hotel employees' coexistence: a helpful tool or a threat to job loss? - Pericleous, Katerina; Liasidou, Sotiroula; Dyankov, Todor (My University, 2025)
Purpose: The aim of the study is to understand employees’ feelings towards artificial intelligence (AI) in relation to their job performance and productivity, as well as their opinion of the risk of being displaced by AI. Design/methodology/approach: The study employed a self-administered questionnaire targeting hotel employees. The results were analysed through exploratory factor analysis to validate constructs and test hypotheses. Findings: In particular, the results of the study indicate employees’ insecurity of job losses when it comes to incorporating AI applications into operational processes. However, it is crucial for employees to understand that embracing AI can boost job productivity, thereby enhancing employee and guest satisfaction. Originality/value: This study is original because it examines a new topic, concerning AI in hotels and evaluates how hotel employees perceive it in relation to their job security.
Keywords: Hotel industry; Guest satisfaction; Artificial intelligence; Job insecurity